Prognostic role of preoperative fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography with an image-based harmonization technique: A multicenter retrospective studyCentral MessagePerspective - Akira Hamada, MD, PhD; Kazuhiro Kitajima, MD, PhD; Kenichi Suda, MD, PhD; Takamasa Koga, MD, PhD; Junichi Soh, MD, PhD; Hayato Kaida, MD, PhD; Kimiteru Ito, MD, PhD; Tetsuro Sekine, MD, PhD; Kyoshiro Takegahara, MD, PhD; Hiromitsu Daisaki, PhD; Masaki Hashimoto, MD, PhD; Yukihiro Yoshida, MD, PhD; et al. (JTCVS Open, 2023)
Objectives: Despite the prognostic impacts of preoperative fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography examination, fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography–based prognosis prediction has not been used clinically because of the disparity in data between institutions. By applying an image-based harmonized approach, we evaluated the prognostic roles of fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography parameters in clinical stage I non–small cell lung cancer. Methods: We retrospectively examined 495 patients with clinical stage I non–small cell lung cancer who underwent fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography examinations before pulmonary resection between 2013 and 2014 at 4 institutions. Three different harmonization techniques were applied, and an image-based harmonization, which showed the best-fit results, was used in the further analyses to evaluate the prognostic roles of fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography parameters. Results: Cutoff values of image-based harmonized fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography parameters, maximum standardized uptake, metabolic tumor volume, and total lesion glycolysis were determined using receiver operating characteristic curves that distinguish pathologic high invasiveness of tumors. Among these parameters, only the maximum standardized uptake was an independent prognostic factor in recurrence-free and overall survivals in univariate and multivariate analyses. High image-based maximum standardized uptake value was associated with squamous histology or lung adenocarcinomas with higher pathologic grades. In subgroup analyses defined by ground-glass opacity status and histology or by clinical stages, the prognostic impact of image-based maximum standardized uptake value was always the highest compared with other fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography parameters. Conclusions: The image-based fluorine-18 fluorodeoxyglucose-positron emission tomography/computed tomography harmonization was the best fit, and the image-based maximum standardized uptake was the most important prognostic marker in all patients and in subgroups defined by ground-glass opacity status and histology in surgically resected clinical stage I non–small cell lung cancers.